Commercial - customers satisfaction in Islamic banking scheme : a case study in Kedah / Noorsaliza Zainal, Zulkafli Mohd. Yusof, Marwan Hashim... [et.al.] - Mohd. Yusof, Zulkafli; Hashim, Marwan; Hassan, Rosli (Institute of Research Management & Innovation, 2005)
Islamic banking scheme (IBS) was officially introduced by Bank Negara Malaysia on March 4 1993. Though many studies had been done on IBS in Malaysia but the studies on customer satisfaction are still new and lacking. This research is designed to identify determinants of customer satisfaction and criteria to select an Islamic bank. The research also determines the differences in customer satisfaction and selection criteria between various customer profiles. This is an empirical research involving two hundred commercial-customers from four selected IBS in Sungai Petani, Alor Star and Kulim. A set questionnaire was distributed to the respective respondents. The data collected was analysed using techniques of frequency distributions, t-test, ANOVA, Kruskal-Wallis and Spearman’s rho rank correlation of Statistical Package for Social Sciences (SPSS) version 12.0. The study found four important results, first, there are ten determinants of customer satisfaction in IBS i.e customer deposits, financing facilities, other products / services, counter service, extra service, bank management, bank staff, advertisement, efficient advice and bank facilities. Second, there are eight criteria to select an Islamic bank, i.e recommendation, confidence, bank image / appearance, bank’s personnel, rate of return, belief and reason, and products offered. Third, there is no difference in satisfaction in IBS across customer profiles except Islamic banks and branches. Finally, there is no difference in selection criteria for an Islamic bank across customer profiles except Islamic banks, branches and occupations. Further research on satisfaction in IBS should be comprehensive, incorporate a larger scope and sample. A comparative study between all IBS banks must be done in order to broaden the generalization of the research findings.